1969
DOI: 10.1111/j.1745-3984.1969.tb00672.x
|View full text |Cite
|
Sign up to set email alerts
|

THE USE OF SEPARATE ANSWER SHEETS BY PRIMARY AGE CHILDREN1

Abstract: The purpose of this study was to determine the effects on test scores of employing a separate answer sheet using the California Test of Mental Maturity with 117 pupils in the primary grades of one through three. The CTMM was administered twice to all students; once employing the usual answer marking format contained in the test booklet and once employing a separate answer sheet. A counterbalanced design was used to control for order effects. The mean raw differences between marking format conditions decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Above fifth grade, subjects were able to make valid responses regardless of the specificity of the instructions rendered. This effort partially replicated a study conducted by Cashen and Ramseyer (1969). They found that first and second graders could not use a separate answer sheet properly but that bright third graders were able to do so.…”
Section: Introductionsupporting
confidence: 56%
“…Above fifth grade, subjects were able to make valid responses regardless of the specificity of the instructions rendered. This effort partially replicated a study conducted by Cashen and Ramseyer (1969). They found that first and second graders could not use a separate answer sheet properly but that bright third graders were able to do so.…”
Section: Introductionsupporting
confidence: 56%
“…As has been reported by previous investigators (cf. Gaffney & Maguire, 1971;Ramseyer & Cashen, 1971;Cashen & Ramseyer, 1969;Loiselle, 1960), test scores are often adversely affected when separate answer sheets are used by lower elementary school pupils. The results of this study confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…The largest study (Beck, 1974) found no statistically significant differences between student performance on answer sheets and in test booklets. Of the smaller studies, three (Clark, 1968;Ramseyer & Cashen, 1971;Wise, Plake, Eastman, & Novak, 1987) found better student performance on test booklets and two (Cashen & Ramseyer, 1969;Solomon, 1971) found no significant differences in student performance whether they marked in their test booklets or on separate answer sheets.…”
Section: Please Scroll Down For Articlementioning
confidence: 94%